Teacher Effectiveness in Developing Cooperative Learning Model towards Interpersonal Intelligence at MIN 1 Rejang Lebong - Anbia, Rejabil (CV Media Inti Teknologi, 2023)
This study aims to investigate the effectiveness of teachers in developing Cooperative Learning models on interpersonal intelligence at MIN 1 Rejang Lebong. Interpersonal intelligence is the ability of individuals to interact with others effectively, understand the feelings and thoughts of others, and be able to work together in a group. This research uses a quantitative approach with a pretest-posttest control group design. The type of research conducted is experimental research. The research sample consisted of two classes at MIN 1 Rejang Lebong, namely one experimental class that applied the Cooperative Learning learning model and one control class that applied conventional learning. The instrument used was a previously validated interpersonal intelligence test. The results showed that teachers who applied the Cooperative Learning model could effectively improve students' interpersonal intelligence. After treatment, the experimental class showed a significant increase in interpersonal intelligence scores compared to the control class. This shows that the Cooperative Learning learning model has a positive impact on the development of students' interpersonal intelligence.